2021
DOI: 10.1002/aenm.202100272
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Unit‐Cell Catalysis of CO2 Electroreduction over Sub‐1 nm Cu9S5 Nanowires

Abstract: As a bridge between nanocrystal catalysts and single‐atom catalysts, single‐unit‐cell catalysts seem at first glance to be unavailable for catalysis due to quantum effects and synthetic difficulties. Here, 24 nm Cu9S5 nanowires are synthesized via the LaMer pathway. Interestingly, when polyoxometalate (POM) clusters are introduced during the nucleation process, the 0.9 nm Cu9S5 nanowires are finally formed via covalent co‐assembly, analog to A–B–A–B‐type block co‐polymerization in the polymer field (“A” and “B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 48 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…We also obtained ''A-B-A-B'' type copolymer-analogue Cu 9 S 5 -PW 12 SNWs. 37 The construction of the showed an average width of 0.9 nm, which was consistent with the size of the Cu 9 S 5 clusters (8.93 Å). The results above demonstrated that the sizes of Cu 9 S 5 -PW 12 SNWs were at the single-unit scale.…”
Section: The Cluster-nuclei Co-assembly Pathwaysupporting
confidence: 72%
See 1 more Smart Citation
“…We also obtained ''A-B-A-B'' type copolymer-analogue Cu 9 S 5 -PW 12 SNWs. 37 The construction of the showed an average width of 0.9 nm, which was consistent with the size of the Cu 9 S 5 clusters (8.93 Å). The results above demonstrated that the sizes of Cu 9 S 5 -PW 12 SNWs were at the single-unit scale.…”
Section: The Cluster-nuclei Co-assembly Pathwaysupporting
confidence: 72%
“…At the microscopic scale, the GdOOH SNWs exhibited high flexibility. As the polarity of the dispersions increased, the GdOOH SNWs could coil themselves to form 37 This journal is © The Royal Society of Chemistry 2022 nanorings (Fig. 4(b)).…”
Section: Polymer-analogue Properties Of Snwsmentioning
confidence: 99%
“…Recently, by introducing polyoxometalate (POM) cluster, Cu 9 S 5 single-unit-cell with sub-nanometer of 0.9 nm was prepared through modulating the nucleation pathway (Fig. 14 a) [ 262 ]. Thus, each unit Cu 9 S 5 cell can be regarded as molecular catalyst functioning as an isolated active site for CO 2 RR.…”
Section: Interface Engineering For Co 2 Rrmentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 262 ]. d Schematic illustration of photosynthesis and photoelectrochemical reduction of CO 2 on chlorophyll and HNTM-Au-SA.…”
Section: Interface Engineering For Co 2 Rrmentioning
confidence: 99%
“…By contrast, metallic Cu 0 dominated surfaces facilitate the selective production of CH 4 . Thus far, a large proportion of the relevant literature works have been focused on Cu precursors with specific single chemical states, such as copper oxide (CuO), [ 10 ] CuN, [ 11 ] CuS, [ 12 ] Cu(OH) 2 , [ 13 ] CuOHFCl, [ 14 ] and Cu‐MOFs. [ 15 ] However, controllable manipulation of the surface chemical state of Cu‐based catalysts to achieve multifunctionality with specificity for a particular type of product remains very challenging.…”
Section: Introductionmentioning
confidence: 99%